2014
DOI: 10.1089/jpm.2013.0473
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Early Integration of Palliative Care in Patients with Incurable Lung Cancer

Abstract: Early and routine involvement of palliative care in patients with incurable lung cancer is acceptable to the majority of treating clinicians. To facilitate early integration of palliative care, palliative care providers need to become front-line team members who provide a high-quality service. Lung cancer clinicians need further education as to the role and benefits of early palliative care, and how best to introduce this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 18 publications
0
71
0
Order By: Relevance
“…Most of the barriers found in this focus group study are confirmed by several previous studies executed in different countries such as England, Germany, Norway, Australia, the United States and Canada. For example, a lack of financial resources is defined in several studies as a major concern (Charalambous, Pallis, Hasan, & O'Brien, ; Johnson, Paul, Girgis, Adams, & Currow, ; vanRiet et al, ; Ward et al, ), as well as the fragmented structure of the healthcare society resulting in difficulties in the communication between professional caregivers (Le et al, ; Neergaard, Olesen, Jensen, & Sondergaard, ; vanRiet et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the barriers found in this focus group study are confirmed by several previous studies executed in different countries such as England, Germany, Norway, Australia, the United States and Canada. For example, a lack of financial resources is defined in several studies as a major concern (Charalambous, Pallis, Hasan, & O'Brien, ; Johnson, Paul, Girgis, Adams, & Currow, ; vanRiet et al, ; Ward et al, ), as well as the fragmented structure of the healthcare society resulting in difficulties in the communication between professional caregivers (Le et al, ; Neergaard, Olesen, Jensen, & Sondergaard, ; vanRiet et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some international research has been conducted on barriers to early integration of palliative care into oncology care in a hospital setting, as perceived by oncologists and organ specialists. The most important barriers found were (a) the lack of knowledge of oncologists about the content of PC and what PC has to offer; (b) the existing societal perception of PC as terminal care resulting in resistance to involving it early from patients, caregivers and physicians in order to maintain hope; and (c) the lack of available financial resources for the integration of PC into oncology care (Aldridge et al, ; Le et al, ; vanRiet et al, ; Ward, Agar, & Koczwara, ). However, no studies have looked into barriers to the early integration of PHC into oncology care.…”
Section: Introductionmentioning
confidence: 99%
“…Other clinician barriers to more widespread use of PC include a belief that they are responsible for providing all of the necessary care for patients with cancer, doubt of the benefit of PC, and previous negative experiences with PC. 11,12,39 These experiences with and misperceptions of the role of PC in combination with physicians’ perceptions of patients’ symptoms and experiences may prevent the wider acceptance of PC. 39 In addition, some evidence shows that patients may not want a PC referral even if offered, which could also further limit PC integration.…”
Section: Challenges and Barriers Of Early Integrated Pc Researchmentioning
confidence: 99%
“…11,12,39 These experiences with and misperceptions of the role of PC in combination with physicians’ perceptions of patients’ symptoms and experiences may prevent the wider acceptance of PC. 39 In addition, some evidence shows that patients may not want a PC referral even if offered, which could also further limit PC integration. 37 …”
Section: Challenges and Barriers Of Early Integrated Pc Researchmentioning
confidence: 99%
“…In summary, the evidence appears strong enough to favour an early intervention of palliative care for patients with lung cancer in all stages. In addition, clinicians seem to accept this integrated approach very well [175].…”
Section: Structure Processes and Time Of Integrationmentioning
confidence: 99%